LC Determination of Gemifloxacin in Bulk and Pharmaceutical Formulation - Ganapathy, S.; Raju, G.V.H.; Sankar, D.G. (Asian Journal of Chemistry, 2010)
An isocratic reversed phase liquid chromatographic (RP-LC) method has been developed and subsequently validated for the determination of gemifloxacin in bulk and pharmaceutical formulation. Separation was achieved with a develosil ODS UG-5 250 × 4.6 mm; 5 μ column and triethylamine buffer (pH adjusted to 3.0 ± 0.05 with orthophosphoric acid):acetonitrile:methanol (65:10:25 v/v) as eluent at a flow rate 1.8 mL/min. UV detection was performed at 273 nm. The method is simple, rapid, selective and stability indicating. The described method is linear over a range of 10.341-82.725 μg/mL. The method precision for the determination of assay was below 0.5 % RSD. The percentage recoveries of active pharmaceutical ingredient (API) from dosage forms ranged from 98.0 to 100.1. The method is useful in the quality control of bulk manufacturing and also in pharmaceutical formulations.